Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Keuangan - Ghina Kemala Dewi; Ashar Basyir (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2023)
This research aims to determine the influence of managerial ownership, institutional ownership, board of commissioners, audit committee and the simultaneous influence of Good Corporate Governance indicators on the financial performance of Bank Raya Indonesia. The type of data used is quantitative data and the data used in this research is secondary data in the form of annual financial reports obtained through IDX and the official Bank Raya Indonesia website. The collection technique uses documentation studies. This research uses multiple linear regression analysis techniques using data processing tools, namely SPSS. The results of this research are that managerial ownership in good corporate governance partially has no effect on the company's financial performance with the test results showing a significance value of 0.115 or greater than 0.05. Institutional ownership of good corporate governance partially has no effect on the company's financial performance with the test results showing a significance value of 0.811 or greater than 0.05. The independent board of commissioners on good corporate governance partially has no effect on the company's financial performance with the test results showing a significance value of 0.354 or greater than 0.05. The audit committee on good corporate governance partially influences the company's financial performance with the test results showing a significance value of 0.008 or less than 0.05. Managerial ownership, institutional ownership, independent board of commissioners and audit committee on good corporate governance simultaneously influence the financial performance of Bank Raya Indonesia, the significance result is 0.006 < 0.05 and obtains a ftable value of 6.39, which means fcount ≥ ftable, namely 20.318 ≥ 6.39.